The association between maternal and foetal factors with birth weight discordance in twins from Yucatan, Mexico - Hugo Azcorra; Luis Rodriguez; Nina Méndez (Taylor & Francis Group, 2021)
Birth weight discordance (BWD) is not an uncommon event in twin pregnancies and can be associated with maternal and newborn characteristics. We aimed to analyse the association between maternal sociodemographic and newborn characteristics with BWD in twin infants born in Yucatan, Mexico, during 2008-2017 (n = 2091 pairs). BWD was calculated as the percentage of birth weight of the heavier twin. We defined three categories of BWD: concordant twins: <15%, mild-discordant: 15-24%, and severe discordant: ≥25%. A multinomial logistic regression model was used to analyse the association between maternal sociodemographic and newborn characteristics with BWD. Seventy-four percent (n = 1547) of twin pairs were classified as concordant, 17% (n = 356) met the criteria for mild-discordance and 9% (n = 188) for severe discordance. The odds for mild-discordance were significantly lower for mothers with medium level of education and in the highest quartile of total twin birth weight (TBW). Opposite-sex twin pairs showed increased odds for mild-discordance compared with same-sex pairs. The odds for severe discordance increased as mothers were in older age groups and decreased as TBW increased. Our rates of BWD are similar to those reported in populations from wealthier countries and maternal age and education, infants' sex, and TBW are associated with BWD.